The limits of GIS: Towards a GIS of place. Issue 3 (13th June 2018) - Giordano, Alberto; Cole, Tim
Abstract: In this article we reflect back on our decade‐long collaboration on the geographies of the Holocaust to argue for a GIS of place. Our previous work on ghettoization in Budapest and on the spatio‐temporal patterns of Jewish persecution in Italy had a marked spatial dimension, both in the research questions we set out to answer and the methods we used, which were largely quantitative. During the course of our research, we progressively came to realize that a spatial perspective favors the voice of the perpetrator and that to fully comprehend and understand the geography of the Holocaust, we needed to engage with the voice of the victim, extend the set of methods and tools used, and broaden our epistemology. While proposing a fully‐fledged model of a qualitative GIS of the places and spaces of the Holocaust is beyond the scope of this article, we: (a) argue for the integration of social network analysis, corpus linguistics, and spatio‐temporal methods and for a mixed‐methods analytical approach and (b) note how the topological and relational foundations we identify as fundamental to a GIS of place parallel the long‐standing call for an "integrated history" of the Holocaust.